Case Report: Malignant peritoneal mesothelioma with TFG-ROS1 fusion responds to crizotinib - Ye, Wei; Li, Peng; Fu, Cong; Zhou, Tong (Frontiers in Oncology, 2025)
BackgroundMalignant peritoneal mesothelioma (MPM) is an exceptionally rare tumor type, and its molecular properties are poorly understood. In recent years, gene rearrangement has been found in a subset of MPMs. However, ROS1 rearrangement has not been previously reported in MPM.Case presentationHere, we present the first case report of MPM with TFG-ROS1 rearrangement in a 56-year-old female with no history of asbestos exposure. The patient did not respond to immunotherapy but exhibited sensitivity to crizotinib with a progression-free survival (PFS) of 6 months. Importantly, we identified ROS1 p.K1991N as a potential acquired drug resistance mutation to crizotinib, suggesting that entrectinib may serve as a targeted therapy to overcome this resistance mechanism.ConclusionROS1 rearrangement could potentially represent a novel driver mutation in MPM, especially in female adults. This case report illustrates the benefits of molecular detection in MPM and underscores the potential for lessons learned from other solid tumors to inform treatment strategies for rare diseases.